Antimicrobial and cytotoxic potential of endophytic actinomycetes isolated from Cinnamomum cassia Presl in Lai Chau Vietnam - Quach , Ngoc-Tung; Vu , Thi-Hanh Nguyen; Phi, Quyet Tien; Nguyen , Quang Huy (Academia Journal of Biology, 2024)
New antimicrobials are urgently needed to combat the threat of multidrug-resistant bacteria worldwide. Our study aimed to access the antimicrobial and cytotoxic profiles of endophytic actinomycetes associated with Cinnamomum cassia Presl taken from a mountainous region in the Northwest of Vietnam. The antimicrobial activity, capability for anthracycline-like compounds production and presence of secondary metabolite-biosynthetic genes were consequently determined. Finally, the cytotoxicity of antibiotic-producing actinomycetes was carried out towards various cancer cell lines. A total of 81 actinomycetes were recovered from different organs (roots, stems, leaves) of Cinnamomum cassia, of which 20/81 isolates exhibited antimicrobial activities against at least one of nine microbial strains. The analysis of 16S rRNA genes indicated that antibiotic-producing isolates were grouped into 4 genera Streptomyces, Micromonospora, Saccharothrix, and Microbacterium, among which Streptomyces was the most prevalent. The presence of biosynthetic genes pks-I, pks-II or nrps was detected in 17/20 of isolates. Five strains of Streptomyces griseorubens LCQ8, Streptomyces variabilis LCQ43, Streptomyces californicus LCQ44, Streptomyces fragilis LCQ75, and Streptomyces beijiangensis LCQ77 exhibited broad-spectrum antimicrobial activity against various pathogens with the MIC values ranging from 16 to 256 µg/mL. Furthermore, characterized strains showed considerable cytotoxicity against MCF-7 cell lines with a 50% inhibition concentration of crude culture extracts of less than 30 µg/mL. The findings demonstrated that Streptomyces species isolated from Cinnamomum cassia in mountainous regions hold the potential for growth inhibition of human disease agents.